How do smoking, vaping, and nicotine affect people with epilepsy and seizures? A scoping review protocol. - Jackson A Narrett; Waleed Khan; Melissa C Funaro; Jeremy J Moeller (PLoS ONE)
Background Epilepsy is a prevalent disease that requires personalized care to control seizures, reduce side effects, and ameliorate the burden of comorbidities. Smoking is a major cause of preventable death and disease. There is evidence that patients with epilepsy smoke at high rates and that smoking may increase seizure frequency. However, there is a lack systematically synthesized evidence on the interactions between epilepsy and seizures and smoking, tobacco use, vaping, and smoking cessation. Methods and analysis This scoping review protocol guided by the Joanna Briggs Institute Manual for Evidence Synthesis and the PRISMA Extension for Scoping Reviews will investigate what is known about the interactions between smoking and epilepsy. This review will include the population of persons with all types of epilepsy or seizures and examine an inclusive list of concepts including tobacco use, vaping, nicotine replacement, and smoking cessation. The MEDLINE, Embase, APA Psycinfo, CINAHL, Cochrane, Scopus, and Web of Science databases will be searched. Following systematic screening of records, data will be charted, synthesized, and summarized for presentation and publication. Ethics and dissemination No ethical approval is required for this literature-based study. The results of this scoping review will be submitted for publication in a peer-reviewed journal. This synthesis will be informative to clinicians and direct further research that may improve health outcomes for people with epilepsy. Registration This protocol is registered with the Open Science Framework (DOI: https://doi.org/10.17605/OSF.IO/D3ZK8).